GENERAL ELECTIONS IN BOSNIA AND HERZEGOVINA IN OCTOBER 2022 - Mijatović, Marko (Political Review, 2023)
In this paper, we will consider the general elections in Bosnia and Herzegovina held on October 2, 2022, and the changes in the electoral legislation that came about by the decision of the so-called High Representative in Bosnia and Herzegovina, Kristijan Šmit, on election night, based on the so-called "Bonn Powers". The main intention of these measures was to unfreeze and speed up the process of forming new authorities in the entity Federation of Bosnia and Herzegovina (and to some extent resolve the political tensions between Bosniaks and Croats that have been present for years and decades), proceeding cautiously to meet Croatian demands. Yet the new solution led to a new type of problem, which significantly complicated the formation of new authorities and led to a new reaction of the High Representative, which was the introduction to new political tensions in the entity of the Federation of Bosnia and Herzegovina, but also in the country as a whole.
Keywords: Bosnia and Herzegovina; political system; elections; election system; political parties; High Representative